1991
DOI: 10.1007/bf00053579
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of agroforestry systems for Illinois, USA: silvicultural and economic considerations

Abstract: Recommended managerial inputs and associated outputs expected from practicing agroforestry on marginal farm lands in the central USA are discussed. Modeled management combinations are based on five timber species, three s~te indices, three timber growth rates, five agricultural crops, all common crop rotations, and three tillage systems. Black walnut (Juglans nigra L.), combined with row crop production, is used to illustrate a specific multicropping alternative. Based on net present value, modeled agroforestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Alley cropping involves growing field crops between rows of trees [72]. The trees can be grown for timber or fruits and nuts, while the alley crops can include a variety of grains, vegetables, or forages cut for hay.…”
Section: Alley Croppingmentioning
confidence: 99%
“…Alley cropping involves growing field crops between rows of trees [72]. The trees can be grown for timber or fruits and nuts, while the alley crops can include a variety of grains, vegetables, or forages cut for hay.…”
Section: Alley Croppingmentioning
confidence: 99%
“…The results presented are the sole responsibility of the authors and/or the University of Missouri and may not represent the policies or positions of the ARS or EPA. nomic analyses conducted by Kurtz et al (1984), Dwyer et al (1990), Campbell et al (1991), and Kurtz (2000) have demonstrated that well-planned forestry systems can provide an above-average long-term return on investment. Even though the conversion of pastures to planned forestry systems could have long-term economic benefits for producers, many landowners feel that it is economically difficult for them to make the change.…”
Section: Introductionmentioning
confidence: 94%
“…There are also numerous row-planting trials concerning agroforestry systems (e.g. Budiantho 1989, Rawat 1991, Campbell et al 1991. Only a few studies of spacing or rowplanting of birchwoods have been done and most of them are from shelterbelt trials in USA or Russia (George 1948, Hogg 1965, Torokhtun 1981, Stadnik 1982, Rakov 1990.…”
Section: Introductionmentioning
confidence: 98%